From generation to generation : the health and well-being of children in immigrant families - Hernandez, Donald J. (Donald James), 1948-; Charney, Evan.; National Research Council (U.S.). Committee on the Health and Adjustment of Immigrant Children and Families (Washington, DC : National Academy Press, 1998)
From Generation to Generation explores what we know about the development of white, black, Hispanic, and Asian children and youth from numerous countries of origin. Describing the status of immigrant children and youth as "severely understudied," this work both draws on and supplements existing research to characterize the current status and outlook for immigrant children. The book discusses the many factors - acculturation, conditions in their receiving communities, parent employment and income, fluency in English, delivery of health and social services, and public policies - that shape the lives of these children and youth. The committee makes recommendations for improved research and data collection designed to advance knowledge about these children and, as a result, their visibility in current policy debates
1. Introduction 2. Shift of Resolve 3. Roadmap 4. Pieces of the Puzzle 5. Opening Closed Doors 6. From Those in the Valley 7. Mandatory Arrest and Restraining Orders 8. A Domestic Violence Prototype: Teaching, Enforcement, and Mediation 9. The Winds of Change 10. Afterword App. I. The National Institute of Justice Studies App. II. Family Disputes App. III. Police Policy and Procedure App. IV. Domestic Violence Policy Involving Law Enforcement Personnel App. V. A Clear and Concise Policy App. VI. Massachusetts General Law C.290A App. VII. Massachusetts General Law 265 S.43, Stalking.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Children of immigrants -- United States; Children of immigrants -- Health and hygiene -- United States; Children of immigrants -- Services for -- United States; Child welfare -- United States; Sociology; Public welfare; Medical care; Demography; National health services; Social sciences; Public health; Child health services; Community Health Services; Population Dynamics; Population Characteristics; Sociology; Social Welfare; Delivery of Health Care; Demography; Health Services; Social Sciences; Epidemiologic Measurements; Anthropology, Education, Sociology and Social Phenomena; Health Care Facilities, Manpower, and Services; Public Health; Environment and Public Health; Emigration and Immigration; Socioeconomic Factors; Child Health Services; Child Welfare; Patient Care; Enfants d'immigrants -- États-Unis.; Enfants d'immigrants -- Santé et hygiène -- États-Unis.; Enfants d'immigrants -- Services -- États-Unis.; Sociologie; Aide sociale; Prestation de soins; Démographie.; Services de santé.; Sciences sociales; Santé publique; Enfants -- Services de santé.; Soins médicaux.; sociology; welfare services; demography; social sciences; public health; SOCIAL SCIENCE -- Children's Studies; Sociology; Social sciences; Public welfare; Public health; National health services; Medical care; Demography; Child health services; Child welfare; Children of immigrants; Children of immigrants -- Health and hygiene